2022
DOI: 10.1186/s13054-022-04248-x
|View full text |Cite
|
Sign up to set email alerts
|

Augmented-Medication CardioPulmonary Resuscitation Trials in out-of-hospital cardiac arrest: a pilot randomized controlled trial

Abstract: Background Previously conducted physician-centered trials on the usefulness of vasopressin have yielded negative results; thus, patient-oriented trials have been warranted. We hypothesize that Augmented-Medication CardioPulmonary Resuscitation could be helpful for selected patients with out-of-hospital cardiac arrest (OHCA). Methods This is a double-blind, single-center, randomized, placebo-controlled trial conducted in the emergency department in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…In this meta-analysis, 26 studies, including 16 RCTs [ 19 34 ] and 10 non-randomized cohort studies [ 35 44 ]) that met the predefined criteria considered. The randomized controlled studies comprised 6 single-centre RCTs [ 19 21 , 23 , 31 , 32 ], eight 8 multi-centre RCTs, and two 2 single-centre non-RCTs [ 39 , 43 ]. Participants were adults aged 30–80, with two exceptions involving ages 15–94 [ 38 ] and 16–21 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis, 26 studies, including 16 RCTs [ 19 34 ] and 10 non-randomized cohort studies [ 35 44 ]) that met the predefined criteria considered. The randomized controlled studies comprised 6 single-centre RCTs [ 19 21 , 23 , 31 , 32 ], eight 8 multi-centre RCTs, and two 2 single-centre non-RCTs [ 39 , 43 ]. Participants were adults aged 30–80, with two exceptions involving ages 15–94 [ 38 ] and 16–21 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, past trials have shown no benefits of vasopressin for ROSC or neurologic outcome over the standard dose of adrenaline, such that its use in CPR was abandoned [ 21 ]. The “Augmented-Medication CardioPulmonary Resuscitation” (AMCPR) trial [ 22 ] is a new pilot RCT on the use of vasopressin during CPR published in 2022. A total of 148 adult non-traumatic OHCA patients with shockable presenting rhythm, who presented a diastolic blood pressure (DBP) < 20 mmHg after insertion of an arterial line at admission to the emergency department, were randomized to receive 40 UI vasopressin or placebo in addition to adrenaline.…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Survival to hospital discharge and good neurologic recovery were also not different between groups. Nevertheless, median DBP during resuscitation was significantly higher in patients receiving vasopressin than in those treated with placebo, likely increasing coronary perfusion pressure during CPR [ 22 ]. Thus, this study does not support the need to modify current recommendations by reintroducing vasopressin as an alternative drug for CPR.…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
See 2 more Smart Citations